Production of Mannan-Degrading Enzymes by Aspergillus Niger in Shake Flasks and Stirred Tank Fermenter - Mohamad, Siti Norita (2005)
Optimization of medium composition and culture conditions for mannan-degrading enzymes production by Aspergillus niger was carried out in shake flasks and 2 L stirred tank fermenter. Preliminary, three potential strains (Sclerotium rolfsii, Rhizopus oryzae and A. niger) were screened, and A. niger was used for subsequent study. The mannandegrading enzymes were purified partially and characterized with regard to pH optima and stability, temperature optima and stability, and Km and Vmax values. The influence of agitation speed, aeration rate and incubation temperature on the production of mannandegrading enzyme in batch fermentation using 2 L stirred tank fermenter were also investigated. Highest level of β-mannanase activity was obtained when guar gum (1495 nkat mL-1) and bacteriological peptone (1744 nkat mL-1) were compared to other carbon (locust bean gum, cellulose, carboxymethylcellulose and glucose) and nitrogen (peptone from meat, yeast extract, ammonium sulphate, nitrate and citrate) sources used. The conditions predicted for the maximum production of β-mannanase through the use of response surface methodology were at pH 5.47, 57 g L-1 bacteriological peptone and 21.3 g L-1 guar gum. The maximal β-mannanase, endoglucanase, β-mannosidase and galactosidase activity obtained from the predicted equation was of 2010.8, 34.8, 1.6 and 39.0 nkat mL- 1, respectively. The optimal temperatures for β-mannanase activity were 50oC and 60oC, with half-life (t1/2) of 6 h at 60oC and 4 h at 70oC. The optimal temperature for endoglucanase activity was 60oC, with t1/2 of 6 h at 60oC and 45 min at 70oC. The optimal temperature for β- mannosidase was 70oC with t1/2 of 1.5 h at 70oC. While the optimal temperature for α- galactosidase activity was 50 to 60oC with t1/2 of 2.5 h at 60oC. The β-mannanase, endoglucanase and α-galactosidase had a pH optima at 3.5 while β-mannosidase at pH 3.0. The enzymes characterized in this study were defined as acidic proteins. The β- mannanase, β-mannosidase, α-galactosidase and endoglucanase showed good stability at pH values of pH 3.5 – 7.0, pH 3.5 – 6.5, pH 3.5 – 5.0 and pH 4 – 7, respectively after a prolonged incubation (24 h at 50oC). High substrate specificity of crude culture filtrate, with low Km value of β-mannanase (0.04 mg mL-1), endoglucanase (0.54 mg mL-1), β- mannosidase (1.67 mM) and α-galactosidase (1.34 mM) indicates the synergistic effect of the enzyme mixture had occurred. The value of Vmax for β-mannanase, endoglucanase, β- mannosidase and α-galactosidase were 0.52, 0.12, 1.72 x 10-3 and 4.68 x 10-3 nmol mL-1 min-1, respectively. A fermentation in 2 L stirred tank fermenter using optimized medium yielded 678 nkat mL-1 β-mannanase, associated with 1.25 nkat mL-1 β-mannosidase, 18.46 nkat mL-1 α- galactosidase and 40.15 nkat mL-1 endoglucanase at impeller tip speed of 0.82 m s-1, aeration rate of 0.1 vvm and incubation temperature of 35oC. Higher degree of agitation speed and aeration rate had an inhibitory effect on the production of mannan-degrading enzymes.